SaRoCy dataset for the object 76 of simulations - Leventis, Georgios; Kyriakidis, Phaedon; Nikolaidis, Andreas (My University, 2022)
This dataset (.zip) contains the results (i.e.trajectories) in csv format derived from the particle tracking simulations for the object 76 in the context of the SaRoCy project, which were running hourly for a 3 days trip for each of the 100 particles that started from the 27 documented locations.
Keywords: SaRoCy; Trajectories; Early Holocene